The quality of corporate governance practices of Tanzania listed firms - Matinde, Emmanuel (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Master of Science in Accounting and Finance (MSc. A&F) at Mzumbe University